2014
DOI: 10.21776/ub.jitode.2014.002.03.02
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Development Strategy of Buntula’bi Balusu Sub-Village, North Toraja Regency Based on Tourist Perception

Abstract: Buntula'bi Balusu Sub-village located in North Toraja Regency. It is uniquely endowed with diverse cultural heritages, both physical (tangible) and non-physical (intangible) cultures, viable to attract domestic and/or international tourists. The objectives of this research were to identify Buntula'bi physical and non-physical characteristics, analyse the tourists' perceptions towards Buntula'bi's tourism objects performances, and formulate the appropriate direction of tourism development within the sub-village… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
(1 reference statement)
0
8
0
1
Order By: Relevance
“…This method was used to analyze tourists' perceptions towards the attributes of tourism objects' performances in order to formulate a tourism development strategy [13] in Sukorambi Botanical Garden. IPA is a combination of perceptions towards the satisfaction and importance level [12].…”
Section: Importance Performance Analysis (Ipa)mentioning
confidence: 99%
See 3 more Smart Citations
“…This method was used to analyze tourists' perceptions towards the attributes of tourism objects' performances in order to formulate a tourism development strategy [13] in Sukorambi Botanical Garden. IPA is a combination of perceptions towards the satisfaction and importance level [12].…”
Section: Importance Performance Analysis (Ipa)mentioning
confidence: 99%
“…Quadrant A/I contain attributes that are considered important by tourists, but the quality of their services has not met their expectations [13]. The tourist attraction must try to improve the attributes in this quadrant to increase customer satisfaction.…”
Section: Quadrant A/i Concentration Here/main Priority (High Importamentioning
confidence: 99%
See 2 more Smart Citations
“…As key priorities in tourism development strategy are formulated to: Improve public facilities, Optimize road condition for better access, Develop more restaurants and accommodations, and Develop souvenir shops [16]. It can be concluded that the existing facilities in tourist destinations is an important component in process of developing tourism destinations.…”
Section: Aggressive Maintenance Strategymentioning
confidence: 99%